What is required to develop career pathways for teaching academics? - Bennett, Dawn; Roberts, Lynne; Ananthram, Subra; Broughton, Michelle (Springer, 2017)
Despite the rise of teaching academic (teaching only) roles in Australia, the UK, the USA, and Canada, the experiences of teaching academics are not well documented in the literature. This article reports from a university-wide study that responded to the introduction of teaching academic roles during a major restructure of academic staff. Thirteen focus groups involving 115 academic staff employed in a range of roles were held approximately 12 months after teaching academic roles were introduced. In conveying the results, we first report on the teaching academic experience, highlighting the perceived low value of the teaching academic (TA) role and confusion about what the role entails. We then focus on teaching academic career pathways. The findings highlight the uncertainty surrounding career paths for teaching academics, who noted the absence of career or promotion scripts. Respondents noted also an absence of role models within the professoriate. They expressed widespread concerns about developing the traditional academic skill set required to transition between roles and institutions, with many TAs finding themselves in boundaried careers with an uncertain future. The construct of career or promotion scripts is used to examine multiple perceptions of career pathways for teaching academics. The findings highlight the importance of systematic change management processes when new academic roles are introduced within the context of university-wide academic restructure, and the critical role of human resources in designing and implementing the same.